2000
DOI: 10.1177/0018726700537004
|View full text |Cite
|
Sign up to set email alerts
|

Moral Awareness in Business Organizations: Influences of Issue-Related and Social Context Factors

Abstract: Individuals' awarenessof moral issues is an important first step in the ethicaldecision-making process. Relying on research in social cognition andbusiness ethics, we hypothesized that moral awareness is influenced byissue-related factors (magnitude of consequences of the moral issueand issue framing in moral terms) and social contextrelated factors(competitive context and perceived social consensus that the issue isethically problematic). The hypotheses were tested in a fieldexperiment involving 291competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(303 citation statements)
references
References 32 publications
13
268
0
12
Order By: Relevance
“…Social consensus works in a similar way: it provides social proof that the moral issue is salient and, thereby, triggers recognition and judgment of that moral issue. Research has shown social consensus to impact moral awareness (Butterfield, Trevino, & Weaver, 2000;Singhapakdi et al, 1996) and moral judgment (May & Pauli, 2002). Likewise, we expect perceptions of social consensus to impact how strongly job applicants recognize and judge the morality of a HR request for social media login information.…”
Section: H3mentioning
confidence: 99%
“…Social consensus works in a similar way: it provides social proof that the moral issue is salient and, thereby, triggers recognition and judgment of that moral issue. Research has shown social consensus to impact moral awareness (Butterfield, Trevino, & Weaver, 2000;Singhapakdi et al, 1996) and moral judgment (May & Pauli, 2002). Likewise, we expect perceptions of social consensus to impact how strongly job applicants recognize and judge the morality of a HR request for social media login information.…”
Section: H3mentioning
confidence: 99%
“…Jones' (1991) framework of moral intensity may thus be applicable. Jones describes how moral dilemmas that have a greater potential magnitude of consequences, and higher probability of occurring, amongst other factors, are considered more morally intense, subsequently influencing patterns of cognition and increasing attention toward moral issues; thereby influencing leadership processes in unique ways (Butterfield, Treviño, & Weaver, 2000;Ferrell & Gresham, 1985;Hunt & Vitell, 1986).…”
Section: Magnitude and Probability Of Consequencesmentioning
confidence: 99%
“…It is not only the number of moral issues that creates room for moral entrepreneurship but also their urgency. The urgency of an issue is its magnitude in terms of potential harm and its proximity in time and space (Butterfield et al 2000). The more urgent an issue, the more morality or an appropriate normative response is required (cf.…”
Section: Opportunity For Moral Entrepreneurship: Moral Issues and Mormentioning
confidence: 99%